A test for conditional independence between response time and accuracy. (8th June 2015) - Bolsinova, Maria; Maris, Gunter
Abstract : An important distinction between different models for response time and accuracy is whether conditional independence (CI) between response time and accuracy is assumed. In the present study, a test for CI given an exponential family model for accuracy (for example, the Rasch model or the one‐parameter logistic model) is proposed and evaluated in a simulation study. The procedure is based on the non‐parametric Kolmogorov–Smirnov tests. As an illustrative example, the CI test was applied to data from an arithmetics test for secondary education.